Completing Square Method

Completing square method : The standard form of quadratic equation is ax 2 + bx + c = 0, where a ≠0

Steps used in finding the roots by completing square method are as follows:

1) a$x^{2}$ + bx + c = 0 2x2+ 9x – 20 = 0 a = 2, b = 9 and c = -20
2) Divide by "a" on both sides
$x^{2}$ + bx/ a + c/a = 0
Divide by "2" on both sides
$x^{2}$ + 9x/ 2 -10 = 0
3) add - c on both sides
$x^{2}$ + bx/a + c/a = 0
- c/a = –c /a
----------------------
$x^{2}$ + bx/a = -c/a
add + 10 on both sides
$x^{2}$ + 9x/2 - 10 = 0
+10 = –20
---------------------
$x^{2}$ + 9x/2 = 10
4) add $b^{2}$/ 4$a^{2}$on both sides
$x^{2}$ + bx/a + $b^{2}$/ 4$a^{2}$ = - c/a + $b^{2}$/ 4$a^{2}$
add $9x^{2}$/4 x $2^{2}$= 81/16
$x^{2}$ + 9x/2 + 81/16 = 10 + 81/ 16
5) $(x + b/2a)^{2}= - c/a+ b^{2}/ 4a^{2}$ $(x + 9/4)^{2}$ = (160 + 81)/16
6) $(x + b/2a)^{2} = (-4ac + b^{2})/ 4a^{2}$ $(x + 9/4)^{2}$ = 241/16
7)$ (x + b/2a)^{2}=( b^{2} - 4ac)/4a^{2}$ $(x + 9/4)^{2} $= 241/16
8) Taking square root on both sides
(x + b/2a) =$\pm ( \sqrt(b^{2}$ - 4ac )/ 2a
Taking square root on both sides
(x + 9/4) = $\pm$ √241 /4
9)Add - b/2a on both sides
x = - b/2a ~+mn~ (√b2 - 4ac )/2a
Add - 9/4 on both sides
x = - 9/4 ~+mn~ √241 /4
10) x = (- b ~+mn~ √b2 - 4ac )/2a x = (- 9 ~+mn~ √241 )/ 4

The roots of the equations are (- 9 + √241 )/ 4 and (- 9 - √241 )/ 4


The easiest way to find the roots of the equation in completing square method :

As we know that ax
2 + bx + c = 0 is the standard quadratic equation.

1) Move 'c' to other side.
2) Make the leading coefficient as 1.
3) Add
(-b/2a)2 on both sides of the equation. Then the left side will be a perfect square and then solve it to find the roots of the equation.

Examples :

1) Find the roots of the equation 9x
2 - 15x + 6 = 0 using completing square method.

Solution :
9x
2 - 15x + 6 = 0

9x
2 - 15x = - 6

Here, leading coefficient = a = 9 , b = -15 and c = 6

Divide the whole equation by 9, we get

x
2 - 15x/9 = - 6/9

x
2 - 5x/3 = - 2/3

Now add (-b/2a)
2 = -[-5/(2 x 3)] 2 = (5/6) 2 both sides

x
2 - 5x/3 + (5/6) 2 = -2/3 + (5/6) 2

( x - 5/6)
2 = -2/3 + 25/36

( x - 5/6)
2 = (-24 + 25)/36

( x - 5/6)
2 = 1/36

x - 5/6 = ~+mn~ 1/6

∴ x = 5/6 ~+mn~ 1/6

x = 5/6 + 1/6 or x = 5/6 - 1/6

x = 6/6 = 1 or x = 4/6 = 2/3

So, roots of the equation are 1 and 2/3.

________________________________________________________________
2) Find the roots of the equation 2x
2 - 5x + 3 = 0 by Completing square method.

Solution :
2x
2 - 5x + 3 = 0

2x
2 - 5x = - 3

Here, leading coefficient = a = 2 , b = -5 and c = 3

Divide the whole equation by 2, we get

x
2 - 5x/2 = - 3/2

x
2 - 5x/2 = - 3/2

Now add (-b/2a)
2 = -[-5/(2 x 2)] 2 = (5/4) 2 both sides

x
2 - 5x/2 + (5/4) 2 = -3/2 + (5/4) 2

( x - 5/4)
2 = -3/2 + 25/16

( x - 5/4)
2 = (-24 + 25)/16

( x - 5/4)
2 = 1/36

x - 5/4 = ~+mn~ 1/4

∴ x = 5/4 ~+mn~ 1/4

∴ x = 5/4 + 1/4 or x = 5/4 - 1/4

∴ x = 6/4 = 3/2 or x = 4/4 = 1

So roots of the equation is 3/2 and 1.

Introduction of Quadratic Equations

Splitting of middle term
Completing square method
Factorization using Quadratic Formula
Solved Problems on Quadratic Equation

Home Page